EDUKASI PENCEGAHAN ANEMIA PADA IBU HAMIL DENGAN MEMANFAATKAN TELUR AYAM NEGERI REBUS UNTUK MENINGKATKAN KADAR HEMOGLOBIN - Gina Nafsa Mutmainna; Desy Syswianti; Tri Wahyuni; Sugiah; N. Ai Erlinawati (LP4M STIKes Karsa Husada Garut, 2023)
The hematological system in pregnant women undergoes significant changes, one of which is an increase of 30-50% in blood plasma with an average increase of 1.5 liters during pregnancy. Other changes in red blood cells, hematocrit and hemoglobin throughout pregnancy do not experience a commensurate increase in blood plasma, an increased supply of iron and vitamins is needed to make hemoglobin because when the body needs more iron than it has available, it can potentially cause anemia. Efforts that can be made to overcome anemia in pregnant women are to consume food sources that contain a lot of iron. Eggs are one source of animal protein. In 1 egg contains 6.5 mg of iron which is divided into 6.3 mg in egg yolk and 0.2 mg in egg white. The implementation of community service activities uses health counseling methods and health checks such as hemoglobin and ANC checks which take place at Posyandu Al Wasilah, Dawungsari Village, Cilawu District, Garut Regency. The results of this activity showed high enthusiasm from the participants and increased participants' understanding of hemoglobin during pregnancy. The conclusion obtained from this service activity is that participants understand the importance of maintaining nutritional intake during pregnancy and know the benefits of eggs in increasing hemoglobin levels for pregnant women.